If \(xyz=-1\), then the value of \( \sqrt [ 4 ]{ \left( xyz \right)^4 } \) is

**Option 1** : 1

Why?

Because

\[\Large{ \sqrt [ 4 ]{ \left( xyz \right)^4} =\sqrt [ 4 ]{ \left( -1 \right) ^{ 4 } } =\sqrt [ 4 ]{ 1 } =1}\]

**Option 2** : -1

Why?

Because

\[\Large{\sqrt [ 4 ]{ \left( xyz \right) ^{ 4 } }=xyz=-1}\]

**Option 3** : \(i\)

Why?

Because

\[\Large{\sqrt [ 4 ]{ \left( xyz \right) ^{ 4 } } =\quad \sqrt [ 4 ]{ \left( xyz \right) ^{ 3 } } \times \sqrt [ 4 ]{ xyz } =\sqrt { i } \times \sqrt { i } =i}\]

Explanation required

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestI think this one example may help you.

Ex. \((\sqrt{-1})^2 \neq \sqrt{(-1)^2}\)

LHS: \((\sqrt{-1})^2 = -1 \)RHS: \(\sqrt{(-1)^2} = |-1| = 1 \)I think all the options are correct. Given equation has 4 roots.i.e \(1 , -1 , \iota , -\iota\)

Log in to reply

let x = xyz^4 so x will have roots ie i,-1,1,one more

Log in to reply

Option 1. First condition: xyz= -1

Log in to reply

Option 1, because the property that (a)^(mn)=a^m*a^n is only preserved for real numbers.

Log in to reply

Option \(0!\)

Log in to reply

option 1 guaranteed .option 2-no because the root sign stands for only positive values and option 3 -no because u cant do it for unreal numbers

Log in to reply

Option 1

Log in to reply

Explanation required

Log in to reply

(x^2n)^(1/2n)=|x|

Log in to reply

Log in to reply

Ya correct explanation.....its option 1

Log in to reply